2011
DOI: 10.1111/j.1438-8677.2010.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of sunflower crop traits and fitness in Helianthus petiolaris populations

Abstract: Transgenic plants have increased interest in the study of crop gene introgression in wild populations. Genes (or transgenes) conferring adaptive advantages persist in introgressed populations, enhancing competitiveness of wild or weedy plants. This represents an ecological risk that could increase problems of weed control. Introgression of cultivar alleles into wild plant populations via crop-wild hybridisations is primarily governed by their fitness effect. To evaluate this, we studied the second generation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 63 publications
(133 reference statements)
0
20
0
Order By: Relevance
“…Hybridization from cultivated to wild populations can threaten the persistence of wild taxa, through either (i) demographic swamping, in which hybrids with reduced fitness decrease population growth rates, or (ii) genetic swamping, in which hybrids with moderate‐to‐high fitness replace pure wild genotypes over time (Todesco et al., ; Wolf, Takebayashi, & Rieseberg, ). It has long been assumed that crop–wild hybrids would have a lower fitness than their wild parent in natural habitats as has been shown, for instance, in sunflowers (Gutierrez, Cantamutto, & Poverene, ). However, in many other cases, hybrids showed no decrease in fitness, for instance in Sorghum (Arriola & Ellstrand, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hybridization from cultivated to wild populations can threaten the persistence of wild taxa, through either (i) demographic swamping, in which hybrids with reduced fitness decrease population growth rates, or (ii) genetic swamping, in which hybrids with moderate‐to‐high fitness replace pure wild genotypes over time (Todesco et al., ; Wolf, Takebayashi, & Rieseberg, ). It has long been assumed that crop–wild hybrids would have a lower fitness than their wild parent in natural habitats as has been shown, for instance, in sunflowers (Gutierrez, Cantamutto, & Poverene, ). However, in many other cases, hybrids showed no decrease in fitness, for instance in Sorghum (Arriola & Ellstrand, ).…”
Section: Introductionmentioning
confidence: 99%
“…Fecundity is commonly used to measure fitness in Helianthus (Burke and Rieseberg 2003;Mercer et al 2006;Whitney et al 2006;Gutierrez et al 2011). However, fecundity may only rarely be the best predictor of population growth rates (Crone 2001).…”
Section: Local Adaptation and The Origin Of An Adaptive Phenotypementioning
confidence: 99%
“…It long dominated the view that crop-wild hybrids have a lower fitness than their wild parent [75,76]. But, many studies confirmed that some hybrids display increased [47], while the other display reduced [77] fitness in comparison with their parents. Displayed fitness depends not only on the crop traits introduced to wild relatives, but also on environmental conditions.…”
Section: Gene Flow From Herbicide-resistant Crops To Wild or Weedy Rementioning
confidence: 99%